2021
DOI: 10.3389/fgene.2021.732432
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genomic and Transcriptome Sequences Reveals Divergent Patterns of Codon Bias in Wheat and Its Ancestor Species

Abstract: The synonymous codons usage shows a characteristic pattern of preference in each organism. This codon usage bias is thought to have evolved for efficient protein synthesis. Synonymous codon usage was studied in genes of the hexaploid wheat Triticum aestivum (AABBDD) and its progenitor species, Triticum urartu (AA), Aegilops tauschii (DD), and Triticum turgidum (AABB). Triticum aestivum exhibited stronger usage bias for G/C-ending codons than did the three progenitor species, and this bias was especially higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Interestingly, this result is similar to GC3s content in gymnosperms such as Ginkgo biloba [31], Gnetifer Hypothesis [32], and most dicotyledons [32][33][34][35]. However, monocotyledons such as Triticum Aestivum [36],Zea Mays [37], Hordeum Vulgare [38], and Oryza Sativa [39] all showed high GC content and tended to end in G/C. RSCU analysis results reveal that similar to most higher plants [40], there is A or T use bias in the genome of C. panzhihuaensis.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, this result is similar to GC3s content in gymnosperms such as Ginkgo biloba [31], Gnetifer Hypothesis [32], and most dicotyledons [32][33][34][35]. However, monocotyledons such as Triticum Aestivum [36],Zea Mays [37], Hordeum Vulgare [38], and Oryza Sativa [39] all showed high GC content and tended to end in G/C. RSCU analysis results reveal that similar to most higher plants [40], there is A or T use bias in the genome of C. panzhihuaensis.…”
Section: Discussionsupporting
confidence: 59%
“…Codon use bias is mainly affected by many factors, including gene base composition, gene length, gene expression level, tRNA abundance, amino acid hydrophobicity, aromaticity, mutation, and selection, among which mutation and selection are the most important factors affecting codon use bias ( Trotta, 2013 ; Chen et al, 2014 ). Analyzing the codon bias characteristics and variations of different species is helpful to understanding the genetic structure and evolution trend of species ( Yang et al, 2021 ; Yu et al, 2021 ). Optimal codon analysis can also provide reference for the genetic expression of host genes.…”
Section: Discussionmentioning
confidence: 99%
“…The overall result indicated that the composition of T is imperative in deciding the gene length; in other words, gene lengths affect the composition of T in genes associated with neurodegeneration. Yang et al (2021) linked a compositional parameter of the GC3 content to gene length, wherein genes shorter than 2,000 bp had a higher GC3 content than longer genes.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, short genes show strong expression, whereas, in plants, long genes show strong expression (Ren et al, 2007). Similarly, composition and gene length are correlated; short genes (<2,000 bp) show an increased percentage of GC3 than do long genes (Yang et al, 2021). A significant positive correlation has been reported between gene length and synonymous CUB in Escherichia coli, whereas a negative correlation has been reported in Drosophila melanogaster and Saccharomyces cerevisiae, which depicts the strong bias toward longer genes to enhance translational efficiency because of selection pressure (Moriyama and Powell, 1998).…”
Section: Introductionmentioning
confidence: 99%